2013
DOI: 10.1002/hep.25882
|View full text |Cite
|
Sign up to set email alerts
|

Studies of IL28B genotype and response to peginterferon in chronic hepatitis B should be stratified by HBV genotype

Abstract: In this issue of HEPATOLOGY, Lampertico et al. 1 present a study of mostly hepatitis B virus (HBV) genotype D hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB) patients treated with peginterferon (PEG-)IFN and show that hepatitis B s antigen (HBsAg) loss was significantly associated with IL28B genotype. Our group recently published a study on the association of IL28B genotype with response to PEG-IFN in HBeAg-positive CHB patients. Favorable IL28B genotypes, CC for rs12979860 and AA for rs129802… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The risk of hepatic decompensation after stopping Nuc therapy is one of the main reasons against cessation of Nuc therapy in patients with cirrhosis. 4 The results of this study further support the collective data that the incidence is not higher than that in patients with cirrhosis who continue long-term Nuc therapy, hence it is not a convincing reason against finite Nuc therapy in patients with cirrhosis. 5 Third, up to 10% of the 6216 ETV-treated patients in Hou et al had been lost to follow-up and not completed this study, as shown in their Supplementary Figure 1.…”
Section: Long-term Outcome Of Entecavir Therapy In Chronic Hepatitis supporting
confidence: 73%
“…The risk of hepatic decompensation after stopping Nuc therapy is one of the main reasons against cessation of Nuc therapy in patients with cirrhosis. 4 The results of this study further support the collective data that the incidence is not higher than that in patients with cirrhosis who continue long-term Nuc therapy, hence it is not a convincing reason against finite Nuc therapy in patients with cirrhosis. 5 Third, up to 10% of the 6216 ETV-treated patients in Hou et al had been lost to follow-up and not completed this study, as shown in their Supplementary Figure 1.…”
Section: Long-term Outcome Of Entecavir Therapy In Chronic Hepatitis supporting
confidence: 73%
“…When the assessment of the IL28B polymorphism was extended to include rs8099917, which was recently shown to improve the prediction of a response to PEG-IFN/RBV therapy in chronic hepatitis C patients with the CT genotype of rs12979860, the favourable rs8099917 TT genotype was found in 100% of the rs12979860 CC patients compared with 31% of CT and 10% of TT patients, only. The 42 rs12979860 CT patients with the rs8099917 TT genotype had a significantly higher rate of SVR and HBsAg seroclearance (23% vs 3%, P = 0.045 and 23% vs 0%, P = 0.007 respectively) (19), suggesting that multiple IL28B polymorphisms may be required to define the pretreatment probability of a virological response at an individual level.…”
Section: Baseline Predictors Of Responsementioning
confidence: 99%